M-Structure and the space A(K,E) - T.S.S.R.K. RAO (Rendiconti di Matematica e delle Sue Applicazioni, 1995)
For a compact convex set K and a Banach space E, under some natural M-structure theoretic conditions on K and E, we show that if the space of affine E-valued continuous functions on K is isometric to the space of E-valued continuous functions on some compact space, then K is a Bauer simplex. These results extend some well known characterizations of Bauer simplexes to the vector valued set up.